Is there only one way of project management theorizing, or are there multiple sector-specific project management domains?. Issue 1 (4th January 2017) - Artto, Karlos A.; Gemünden, Hans Georg; Walker, Derek; Peippo-Lavikka, Pirjo
Abstract : Purpose: Many literature reviews on project management (PM) research are limited to studies published only in PM journals but some reviews do expand their analysis on PM research published also in journals belonging to the management studies field. However, the authors found no previous literature reviews comparing the PM content in different sectors outside the management studies field. Therefore, the analysis and findings of PM content derived from the sector-specific engineering and technology-focused journals are new. The paper aims to discuss this issue. Design/methodology/approach: The authors analyze PM content in nine different sectors, where each sector and its inherent research is connected to specific engineering, technological, or industry-related disciplines. The authors conduct an evidence-informed literature review on PM knowledge in the distinct literatures of these nine sectors. The period of analysis is 24 years from 1986-2009. The authors discuss potential consequences of the findings' sector-specificity for future PM domain development. Findings: The perspective on different origins of PM leads to a meta-level PM concept covering several different PM domains, each with its own sector specific and separated development path. Research limitations/implications: The literature analysis purposefully excluded PM journals and management studies, and the authors focused only on sector-specific engineering and technology-focused journals that represent knowledge and wisdom of different PM contents in nine sectors. Practical implications: The findings have significant potential to contribute to scholarly discussion on the development of a universal PM theory. For applicability across sectors, the authors suggest a modular PM theory with different sector-specific modules for knowledge, concepts, and underlying assumptions. Originality/value: Currently, this discussion has been mainly focused on theorizing concepts and approaches in management studies only. This study expands the understanding to engineering and technology-focused journals across nine industry sectors/domains.